Analisis Fundamental Terhadap Harga Saham yang Terdaftar di Jakarta Islamic Index Tahun 2010-2017 - Annisa Masruri Zaimsyah (ITB AAS INDONESIA Surakarta, 2019)
This study discusse the influence Book Value (BV), Price Book Value (PBV), Earning Per Share (EPS) Debt to Equity Ratio (DER), Price to Equity (PER) and Share prices of companies listed on the Jakarta Islamic index (JII). JII chosen because this index is a sharia index with good fundamental character, large capitalization and risk. The data used this research is secondary data from the financial stetements of the companys that became the sample of the research from the official website Indonesia Stock Exchange. Sampel this research to 18 companys period 2013-2017. The results show that variable BV and DER does not affect stock prices but variable PBV, EPS and PER effect on stock prices